The continuity of aboriginal customs and government under British imperial constitutional law as applied in colonial Canada, 1760-1860 - Walters, M (1995)
This thesis examines the British legal status of aboriginal customary laws and governments in colonial Canada between 1760 and 1860, with a view to contributing to the debate about their modern legal status under the Canadian constitution. By "colonial Canada" is meant the British colonies of Quebec (1763-1791), Upper and Lower Canada (1791-1841) and Canada (1841-1867). The central argument of the thesis is that there existed in colonial Canada two distinct systems of municipal law one system for settlers and one system (or set of systems) for natives both deriving legitimacy from an over-arching British imperial constitution. The settler system was established by imperial statute, while native systems were recognized by non-statutory principles of imperial law, or "imperial common law". It is argued that the common-law principle of continuity—according to which British courts presumed that the laws of peoples subjected to British sovereignty remained in force at common law until abrogated by prerogative or Parliamentary legislation formed the doctrinal foundation of aboriginal rights to customary law and government in colonial Canada. The objective of Part One of the thesis is to construct a theory of imperial law applicable to the unique constitutional history of colonial Canada. To this end, the principle of continuity is analysed both as it was developed in relation to England's early imperial experiences and as it was manifested in statutes and judicial opinions relating to native nations in British North American colonies of the seventeenth and eighteenth centuries. Part Two of the thesis applies the general principles of imperial law developed in Part One to Canadian constitutional history. The various municipal legal regimes established under imperial statute for settlers are examined in light of the fact that the imperial ministry, which retained direct control over Indian policy in Canada until 1860, recognized the continuity of native customary law and government in both unceded and reserved Indian lands. It will be argued that this imperial recognition confirmed the common-law continuity of native law and government.